Cardiovascular Disease and Hepatitis C Virus Infection. Issue 1 (January 2015) - Katsi, Vasiliki; Felekos, Ioannis; Skevofilax, Stamatios; Aggeli, Constantina; Tousoulis, Dimitris; Stefanadis, Christodoulos; Kallikazaros, Ioannis
<x xml:space="preserve">Abstract</x> Hepatitis C virus (HCV) is well known for being the leading cause of hepatocellular carcinoma and cirrhosis, contributing to a devastating array of metabolic dysfunctions associated with hepatic failure. However, the cardiac manifestations of HCV and chronic hepatitis C (CHC) are being explored, thus illuminating the connection between HCV infection and cardiac disease. Although not all studies agree, the evidence in favor of CHC promoting major risk factors for cardiovascular disease such as hypertension, insulin resistance, diabetes mellitus, and atherosclerosis is compelling. Similarly, properly warranted attention is being guided towards CHC as an independent risk factor for the development of atherosclerotic heart disease and cardiomyopathy. This review provides a synopsis on the relationship between (HCV) infection and cardiac disease, emphasizing on some of the key possible mechanisms and population derived data.